2001
DOI: 10.1081/ncn-100107200
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antiviral Evaluation of N-Glycosides Derived From 6-Amino-3-Aryl-2-Methyl-4-(3h)-Quinazolinones

Abstract: Reaction of monosaccharides (D-glucose. D-galactose, D-xylose or L-arabinose) with 6-amino-3-aryl-2-methyl-4-(3H) quinazolinones (1a-c) in boiling methanol yielded the corresponding N-glycopyranosides 3a-c, 4a-c, 5a,b and 6a,b. The N-glycopyranosides 3a-c, 4a-c, 5a,b and 6a,b were acetylated with acetic anhydride and pyridine to give the corresponding acetate derivatives 7a-c, 8a-c, 9a,b and 10a,b. The structures of all these glycosides were assessed by elemental analysis, IR, NMR and mass spectra. Some of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
4
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…In the 1 H NMR spectrum, the anomeric proton appeared as a triplet (at δ 4.50) due to the coupling with neighboring NH and CH protons. These NMR data were consistent with those reported (δ C 84.9 and δ H 4.43) for related β- N -glucosides, indicating 5 to be the β- N -glucosylation product. The presence of a signal due to a chelated NH 2 at δ 8.41 in its 1 H NMR spectrum further confirmed that the glucosylation occurred at the C-2 amino group.…”
supporting
confidence: 91%
“…In the 1 H NMR spectrum, the anomeric proton appeared as a triplet (at δ 4.50) due to the coupling with neighboring NH and CH protons. These NMR data were consistent with those reported (δ C 84.9 and δ H 4.43) for related β- N -glucosides, indicating 5 to be the β- N -glucosylation product. The presence of a signal due to a chelated NH 2 at δ 8.41 in its 1 H NMR spectrum further confirmed that the glucosylation occurred at the C-2 amino group.…”
supporting
confidence: 91%
“…On the other hand, various therapeutic activities have been reported for both pyrazole [ 10 , 11 , 12 ] as well as pyrimidine moieties [ 13 , 14 ]. As a part of our continued program on the chemistry of 3H-quinazolin-4-one ring systems, we recently developed a simple and efficient approach to a wide range of such derivatives [ 15 , 16 , 17 , 18 , 19 , 20 ]. These results prompted us to synthesize a series of novel 3H-quinazolin-4-one derivatives containing a pyrazolinone, pyrazole or pyrimidinone ring, with the aim of obtaining some novel heterocyclic systems with potentially enhanced biological properties.…”
Section: Introductionmentioning
confidence: 99%
“…14 gives mp 136-139 °C. 1 H NMR (DMSO-d 6 ): δ (ppm) 8.91 (dd, 1H, J = 1.5, 7.2 Hz), 8.85 (dd, 1H, J = 1.5, 9.4 Hz), 7.74 (s, 1H), 7.35 (ddd, 1H, J = 1.2, 6.3, 9.3 Hz), 7.14 (ddd, 1H, J = 1.5, 6.4, 7.2 Hz), 5.41 (s, 2H), 4.31 (q, 2H, J = 7.2 Hz), 1.34 (t, 3H, J = 7.2 Hz).General procedure for synthesis of N-glycosides (ref 15. ) A mixture of appropriate heterocyclic amine 5 (1.5 mmol) and sugar (1.5 mmol) was refluxed in MeOH (6 mL) in the presence of acetic acid (0.3 mL) for 2 h. Mixture was then cooled and precipitated product was collected by suction and dried on air.…”
mentioning
confidence: 99%